2021
DOI: 10.48550/arxiv.2106.01238
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ODE/IQFT correspondence for the generalized affine $\mathfrak{ sl}(2)$ Gaudin model

Gleb A. Kotousov,
Sergei L. Lukyanov

Abstract: An integrable system is introduced, which is a generalization of the sl(2) quantum affine Gaudin model. Among other things, the Hamiltonians are constructed and their spectrum is calculated within the ODE/IQFT approach. The model fits within the framework of Yang-Baxter integrability. This opens a way for the systematic quantization of a large class of integrable non-linear sigma models. There may also be some interest in terms of Condensed Matter applications, as the theory can be thought of as a multiparamet… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
(56 reference statements)
1
4
0
Order By: Relevance
“…In the context of the Kondo problems and their relation to four-dimensional Chern-Simons theory, these ODE take particular form which depends on the one-form ω underlying the four-dimensional setup. This is in agreement with the fact, mentioned in subsection 5.4, that the four-dimensional Chern-Simons theory is related to the so-called affine Gaudin models: indeed, it was proposed in [5] that these models can serve as a natural framework for studying the ODE/IQFT correspondence (see also [40,98,100,101] for further developments on the quantisation of affine Gaudin models and their relation to the ODE/IQFT correspondence).…”
Section: Quantisationsupporting
confidence: 85%
See 1 more Smart Citation
“…In the context of the Kondo problems and their relation to four-dimensional Chern-Simons theory, these ODE take particular form which depends on the one-form ω underlying the four-dimensional setup. This is in agreement with the fact, mentioned in subsection 5.4, that the four-dimensional Chern-Simons theory is related to the so-called affine Gaudin models: indeed, it was proposed in [5] that these models can serve as a natural framework for studying the ODE/IQFT correspondence (see also [40,98,100,101] for further developments on the quantisation of affine Gaudin models and their relation to the ODE/IQFT correspondence).…”
Section: Quantisationsupporting
confidence: 85%
“…Let us finally mention that in the work [29], it was shown that certain integrable systems called Kondo problems can also be related to the four-dimensional Chern-Simons theory. Quantum aspects of these systems are discussed in [29], in particular in the framework of the so-called ordinary differential equations (ODE)/integrable quantum field theory (IQFT) correspondence [93][94][95][96] (see also [97] for previous results on the ODE/IQFT correspondence for Kondo problems and [40,98,99] for further recent developments). This correspondence relates certain observables of an IQFT, in particular the spectrum of its commuting operators, to the properties of some well-chosen ODE.…”
Section: Quantisationmentioning
confidence: 99%
“…Anisotropic vs coset: from the ODE (4.1), it is interesting to perform a change of coordinate y = e − x and we find e 2θ −2 y −(2+ 2 ) i (1 − g i y) k i + t(y) (4.3) where t(y) ≡ −2 y −2 t(x) − 1 4y 2 . This is precisely the ODE proposed in equation (7.7) of [53]. On the other hand, according to [16], it describes a Kondo defect in a coset su(2) −(2+ 2 ) ⊕ i su (2)…”
Section: Future Directionsmentioning
confidence: 61%
“…Note added: While the manuscript is close to completion, we became aware of [53] which has some overlap with our results. In particular, our proposal of the ODE (3.17) and (4.1) is equivalent to (7.7) in [53] via a suitable change of coordinate. We thank Gleb A. Kotousov and Sergei L. Lukyanov for sharing their work with us before publishing.…”
Section: Introductionmentioning
confidence: 74%
“…In the related quantum toroidal setting such relation is understood thanks to so-called Miki automorphism [63] which exchanges the mode and spin spaces (which is geometrically related to fiber-base duality [64]) and the fact that there can be different systems of Bethe ansatz equations associated to the same physical system is an example of more general phenomenon called spectral duality [65][66][67][68]. There is also a close connection to (affine) Gaudin models, starting from [24] and recently discussed for example in [69][70][71][72][73].…”
Section: Discussionmentioning
confidence: 99%